On Fundamental Theorems for Holomorphic Curves on the Annuli - Phuong, H.T.; Thin, N.V. (Український математичний журнал, 2015)
We prove some fundamental theorems for holomorphic curves on the annuli crossing a finite set of fixed hyperplanes in the general position in ℙn(ℂ) with ramification. Доведено дєякі фундаментальні теореми для голоморфних кривих на кільцях, що перетинають скінченну множину фіксованих гіперплощин загального положення в Pn(C) з розгалудженням.